Diagnóstico do gerenciamento dos resíduos de serviços de saúde da Unidade de Pronto Atendimento, Tucuruí-Pará - PEREIRA, Aline Carolina (2023)
The disposal of Solid Waste from Health Services (RSS) without compliance with the legislation causes damage to the environment and human health. Therefore, this study sought to analyze the management of the RSS, of the Emergency Care Unit - UPA, located in the Santa Monica neighborhood, municipality of Tucuruí-Pará. Checking compliance with the procedures implemented on site with the requirements of the Resolution of the Collegiate Board of Directors (RDC), No. 222, of March 28, 2018. Also, an analysis of the perception of health professionals at the unit was carried out regarding the management of RSS and its adjustments, in order to provide an understanding of its risks. Finally, through the results found, it is possible to understand the challenges in complying with legal standards, the need to apply a Health Services Waste Management Plan, as well as the investment in environmental education, among other proposed improvements.